Adaptive Control of Lactic Acid Production Process from Wheat Flour. Issue 8 (2015) - Gonzalez, Karen Vanessa; Tebbani, Sihem; Dumur, Didier; Lopes, Filipa; Pareau, Dominique; Thorigné, Aurore; Givry, Sébastien
Abstract: The key feature of this paper is the development of a control strategy for the lactic acid production process from wheat flour in a continuous bioreactor. As lactic acid has inhibition effects on bacterial growth and its own production, the regulation of its concentration is required. In this paper, a control strategy is proposed in order to maximize the process productivity. First, the optimal setpoint is determined. Then, a controller based on a state-feedback linearizing control strategy is proposed to regulate the product concentration at its optimal value. The developed control law requires measurement or estimation of online state variables and a good knowledge of model parameters. In this paper the estimation of lactic acid production rate is proposed as an alternative to reduce the complexity of the control law. Different production rate estimators are studied and tested. Finally, the proposed control strategy results in a controller that involves the estimation of the production rate by a Kalman filter. The effectiveness of the developed strategy is illustrated by simulation results.